The human crystallin gene families - Wistow, Graeme (BioMed Central, 2012)
Crystallins are the abundant, long-lived proteins of the eye lens. The major human crystallins belong to two different superfamilies: the small heat-shock proteins (α-crystallins) and the βγ-crystallins. During evolution, other proteins have sometimes been recruited as crystallins to modify the properties of the lens. In the developing human lens, the enzyme betaine-homocysteine methyltransferase serves such a role. Evolutionary modification has also resulted in loss of expression of some human crystallin genes or of specific splice forms. Crystallin organization is essential for lens transparency and mutations; even minor changes to surface residues can cause cataract and loss of vision.